ACUTE TOXICOLOGICAL PATHOLOGY OF COUMAPHOS (ORGANOPHOSPHATE COMPOUNDS) IN ROCK DOVE - Qiesar.A.K (Basrah Journal of Veterinary Research)
The aim of this study was to examine the acute toxicity of organophosphorous insecticide (coumaphos) in wild pigeons (Rock dove) and measure the level of liver enzyme Alanine Transaminase (ALT)in the serum of pigeons treated orally with a single dose 3mg/kg bw. of coumaphos and study the histopathological changes of central and peripheral nervous system ,liver, kidney, heart and pancreas after 3 weeks of dosing .The results showed muscarinic, nicotinic and central nervous system effects and as well as showed a significant increasing (p≤0.‏05) in the level of ALT in the serum of treated pigeons in comparism with control group .The histopathological results included degeneration of nerve fibers in sciatic nerve,spinal cord and hepatocyte also preiportal and septal fibrosis and bile duct proliferation,the kidney showed degeneration of renal tubules and separation of renal capsule